Pemetaan potensi daerah untuk pengembangan kawasan minapolitan di beberapa lokasi dalam Provinsi Aceh: suatu kajian awal - Muchlisin Z. Abidin; Muhammad Nazir; Musri Musman (Depik, 2012)
Abstract. The objective of the present survey was to map the potency of locations for developing of minapolitan area in Aceh province. The survey was conducted on November-December 2011 and it was focused on the four districts i.e. Aceh Jaya, Aceh Besar, Bireuen and Aceh Timur. The data were categorized into two types, i.e. secondary data which was compiled from annual reports, research report and other references. The primary data were collected throught direct and indirect interviewed the key persons in fisheries sector by using the questionnaire. Primary data were also obtained by direct observation in the fields. The results showed that every site has the advantages and disadvantages. However, generally all of the locations have potency to be developed as minapolitan region. Minapolitan models that can be developed are the combination between of capture fisheries, aquaculture, processing and marine tourism. Keywords: Capture fihery, aquaculture, fish processing industry and marine tourism